Partner conflict during their index pregnancy and its correlates among a cohort of six weeks postpartum women in Ethiopia - Solomon Abrha Damtew; Niguse Tadele Atnafu; Mahari Yihdego Gidey; Tesfamichael Awoke Sisay; Metages Yohannes (Scientific Reports)
Abstract Current intimate partner violence (IPV) during pregnancy was found to be associated with adverse health outcomes including pregnancy loss, preterm labor, pregnancy complications, hypertension, delivering low birth weight baby, physical injuries and stress. IPV in Ethiopia is considerably high. This study aimed at determining the prevalence of the IPV during the index pregnancy as measured at six weeks postpartum among women in their extended six weeks postpartum period and identify its correlates. Documenting the magnitude of IPV during the index pregnancy as measured six weeks in the postpartum period and identifying factors affecting it could be imperative to generate actionable evidence. Generating such an evidence contributed its share for the Health Minister and other relevant partners in tracking progress towards achievement of the sustainable development goals (SDGs) 5.2.1 by 2030. This study used Performance Monitoring for Action Ethiopian (PMA_ET) merged cohort one baseline and six weeks postpartum data which had enrolled and collected data from currently pregnant women. Frequencies were computed to describe the study participant’s characteristics, and chi-square statistics was calculated to assess cell sample size adequacy. Multilevel binary logistics regression statistical modeling was employed to identify correlates of IPV. Results were presented in the form percentages and odds ratio with 95% Confidence Intervals. Candidate variables were selected using p-value of 0.25. Statistical significance was declared at p-value of 0.05. The overall proportion of IPV during the index pregnancy as measured six weeks postpartum was 12.14% (95%CI: 10.66%, 13.79%). A slightly higher percentage of women reported that they have experienced at least one form of sexual IPV 8.09% (95% CI: 6.91%, 9.44%) than experiencing at least one form of physical IPV 6.02% (95% CI: 4.94%, 7.31%). After controlling confounders, the likelihood of experiencing at least one form of physical and/or sexual IPV was 2.14 (95%CI: 1.04, 4.38) times higher among women whose husband had other wives’ compared to those who did not have. Women who were residents of Afar region had only 0.14 (95%CI: 0.03, 0.79) odds of experiencing one form of physical and/or sexual IPV. The overall experience of at least one form of physical and/or sexual IPV was found to be 12.14%. A statistically non-significant slightly higher percentage of women reported that they have experienced at least one form of sexual IPV than experiencing at least one form of physical IPV. Activities and efforts which are specific to regions are needed to address the problem of polygamy are hoped to address the problem IPV during pregnancy. Such activities should be tailored along with the maternal and new born care continuum. Further implication of this study is installing violence and contraceptive related preconception care packages in the health system which is imperative in the combat against IPV and any form of gender based violence. In addition, creating institutional capacity in the health system through strengthening and expanding one stop centers to provide medical treatment, care, and psychosocial support along with support for victims and survivors can be considered as imperative. Moreover, the finding gave an insight that installing rapid referral system and linkage to the legal system is key. Similarly, working on early marriage and counseling on childbirth; and spaced pregnancies for those young couples is implied on. Most importantly, determining the prevalence of violence could serve as one of the indicators to monitor the progress towards SDG 5.2.1 and to look for any strategy and policy changes needed in light of the observed progress.